2014
DOI: 10.1080/00387010.2013.803207
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy–Based Multivariate Statistical Analysis Reveals the Molecular Mechanism of K562 Cell Apoptosis Induced by Adriamycin

Abstract: Based on the combination of Raman spectroscopy with principal component analysis and hierarchical cluster analysis, the molecular mechanism of K562 cell apoptosis induced by Adriamycin in physiological conditions is presented. The obtained results reveal that DNA of K562 cells treated with Adriamycin is lowered greatly, indicating that the damage of the DNA of K562 cells is indeed the main molecular mechanism of K562 cell apoptosis induced by Adriamycin. Specially, by combining principal component analysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Raman spectroscopy is a nondestructive method that reveals the structure and bond vibration information of targeted molecules and serves as a strong tool for biological research. , Raman spectroscopy has been applied to the detection of cell states and the identification of different types of tumor cells. , It is also reported that Raman spectroscopy can successfully distinguish lymphoma cells from normal lymphocytes . However, the relative small cross section of the Raman scattered light of biomolecules hinders further enhancement of the detecting sensitivity of molecules .…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy is a nondestructive method that reveals the structure and bond vibration information of targeted molecules and serves as a strong tool for biological research. , Raman spectroscopy has been applied to the detection of cell states and the identification of different types of tumor cells. , It is also reported that Raman spectroscopy can successfully distinguish lymphoma cells from normal lymphocytes . However, the relative small cross section of the Raman scattered light of biomolecules hinders further enhancement of the detecting sensitivity of molecules .…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Furthermore, Raman spectra of biomolecules can be used in classication models to identify the location of particles in cells, [19][20][21][22][23] and also to quantify possible particleinduced chemical changes. [24][25][26][27][28][29][30][31][32][33] This makes Raman spectroscopy a tool for not only measurements of the number of cells with internalized particles or particles attached to the cell surface, but also for analysis of possible biochemical alterations induced by the particles.…”
Section: Introductionmentioning
confidence: 99%